2012
DOI: 10.1038/pr.2012.167
|View full text |Cite
|
Sign up to set email alerts
|

Brain inflammation induced by severe asphyxia in newborn pigs and the impact of alternative resuscitation strategies on the newborn central nervous system

Abstract: Background:We compared the current guidelines for neonatal resuscitation with alternative measures and aimed to find out whether this modulated brain inflammation. Methods: Progressive asphyxia was induced in 94 newborn pigs until asystole. With the reference being resuscitation guidelines, 30 s of initial positive-pressure ventilation before compression (c) and ventilation (V) (c:V; 3:1) in 21% oxygen, pigs were randomized to (i) ventilation for 30, 60, or 90 s before chest compressions; (ii) c:V ratios of 3:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 38 publications
0
30
0
1
Order By: Relevance
“…[216][217][218][219][220][221][222][223] 222 One demonstrated more rapid restoration of cerebral blood flow but no difference in histologic brain injury scores. 224 For the critical outcome of oxidative injury, we found 10 animal studies reported on oxidative injury with varying results 212,213,216,[219][220][221][222][223][225][226][227] (very-low-quality evidence, downgraded for potential bias, inconsistency, and indirectness). Six studies (pigs/mice) demonstrated no difference in various oxidative injury markers, 212,213,[219][220][221]224 3 (lambs/ rats) demonstrated more oxidative damage from using 100% O 2 including apoptosis, 216,222,226 and a pig study reported less striatal and hippocampal apoptosis with 100% O 2 compared with 21% O 2 .…”
Section: Consensus On Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…[216][217][218][219][220][221][222][223] 222 One demonstrated more rapid restoration of cerebral blood flow but no difference in histologic brain injury scores. 224 For the critical outcome of oxidative injury, we found 10 animal studies reported on oxidative injury with varying results 212,213,216,[219][220][221][222][223][225][226][227] (very-low-quality evidence, downgraded for potential bias, inconsistency, and indirectness). Six studies (pigs/mice) demonstrated no difference in various oxidative injury markers, 212,213,[219][220][221]224 3 (lambs/ rats) demonstrated more oxidative damage from using 100% O 2 including apoptosis, 216,222,226 and a pig study reported less striatal and hippocampal apoptosis with 100% O 2 compared with 21% O 2 .…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Animal studies demonstrate no advantage to higher compression-to-ventilation ratios (very-low-quality evidence, downgraded for potential bias, indirectness, and imprecision) regarding Short-term survival (2 randomized controlled trials including 54 pigs) 210,211 Gas exchange during CPR (2 randomized controlled trials including 54 pigs) 210,211 Time to ROSC (2 randomized controlled trials including 54 pigs) 210,211 Markers of tissue injury (lung/ brain) (2 randomized controlled trials including 54 pigs) 212,213 There was no evidence identified to address the critical issue of neurologic outcome.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…The chest should be allowed to re-expand fully during relaxation, but the rescuer's thumbs should not leave the chest. The Neonatal Resuscitation ILCOR and Guidelines Task Forces continue to support use of a 3:1 ratio of compressions to ventilation, with 90 compressions and 30 breaths to achieve approximately 120 events per minute to maximize ventilation at an achievable rate [173][174][175][176][177][178] (Class IIa, LOE C-LD). Thus, each event will be allotted approximately a half of a second, with exhalation occurring during the first compression after each ventilation.…”
Section: Chest Compressions Nrp 605 Nrp 895 Nrp 738 Nrp 862mentioning
confidence: 99%
“…Because the 2-thumb technique can be continued from the head of the bed while the umbilicus is accessed for insertion of an umbilical catheter, the 2-finger technique is no longer needed. [173][174][175][176][177][178] (Class IIa, LOE C-LD). Thus, each event will be allotted approximately a half of a second, with exhalation occurring during the first compression after each ventilation.…”
mentioning
confidence: 99%